Training and competition loads in women`s rugby sevens athletes: Are there implications for cardiovascular health? - Luca Napoli, Stuart Semple, Andrew J. McKune (International Journal of Sports Physiology and Performance, 2023)
National- and international-level rugby sevens athletes are exposed to high training and competition loads over the course of a competitive season. Research on load monitoring and body-system responses is widespread; however, the primary focus has been on optimizing performance rather than investigating or improving cardiovascular health. There is a degree of cardiovascular remodeling, as well as local and systemic inflammation, in response to excessive exercise. These responses are moderated by many factors including previous exercise exposure, current exercise intensity and duration, age, race, and gender, as well as sport-specific physiology. For these reasons, high-performing female rugby sevens athletes may have a unique cardiovascular risk profile different from males and other rugby codes. This review aimed to characterize the training and competition loads, as well as the anthropometric and physiological profiles, of female rugby sevens athletes; discuss the potential impacts these may have on the cardiovascular system; and provide recommendations on future research regarding the relationship between rugby sevens training and competition loads and cardiovascular health. Movement demands, competition formatting, and training routines could all contribute to adverse cardiovascular adaptations. Anthropometric data and physiological characteristics may also increase the risk of cardiovascular disease. Future research needs to adopt measures of cardiovascular health to obtain a greater understanding of cardiovascular profiles and risk factors in female rugby sevens athletes.